Uses of Prediction in Secondary Schools - Herman, Al; Gallo, Joseph G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Predictive validity of the Differential Aptitude Test (DAT) was investigated by comparing the DAT scores obtained by students in Grade IX against their achievement in Grade XII departmental examinations. Results indicated that the DAT has good predictive power and can be used effectively on a selective basis for counseling and predictive purposes in high schools.